Землі Придунав’я і Рим в історіографії ЧССР - Лісовий, І.А. (Археологія, 1989)
В статье обобщаются достижения чехословацких ученых по вопросу контактов Рима с Придунавьем. Подчеркивается, что он исследовался в следующих аспектах: углубленное и всестороннее изучение источников, в том числе памятников материальной культуры; анализ взаимоотношений чехословацких земель с Римом, этнокультурного и политического развития Среднего Придунавья; исследование экономических и военно-политических отношений в Придунавье, исторического развития Паннонии в связи с началом кризиса империи, а также других придунайских провинций. Анализируются работы 3. Неедлы, И. Добиаша, Б. Свободы, В. Ондроуха, О. Пеликана, П. Оливы, Л. Видмана, К. Курца, Т. Колника, В. Сакаржа, Я. Тейрала и других чехословацких исследователей. Achievements of the Czechoslovak scientists concerning the problem on contacts of Rome with the Danube area are generalized in the paper. It is emphasized that the above problem has been studied in the following aspects: profound and thorough studies of sources including monuments of material culture; analysis of relations between the Czechoslovak lands and Rome; ethnocultural and political development of the Middle Danube area, investigation of economic and military-political relations in the Danube area, historical development of the Pannonian as a result of the beginning of the crisis in the empire and in other Danube provinces. Works by Z. Nejedly, J. Dobias, B. Svoboda, V. Ondrouch, O. Pelikan, P. Oliva, L. Vidman, K. Kurz, T. Kolnik, V. Sakaf, J. Tejral and other Czehoslovak researchers are analyzed.